2018
DOI: 10.1080/01480545.2018.1483945
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive components in Ghost chili (Capsicum chinense) for antioxidant, genotoxic, and apoptotic effects in mice

Abstract: Apart from using traditionally in culinary preparations, chili peppers are also important constituents of herbal medicines. Although the bioactive components are studied mostly in the fruits of Capsicum annuum, no such study reports till date is available for Ghost chili (C. chinense) from North East India. Therefore, the aim of this study was to carry out an analysis of the bioactive constituents in the naturally occurring hottest chili Ghost chili (C. chinense), and evaluate its antioxidant, pro/anti-genotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…As reported by Bertão et al (2016), TPC in ethanol extracts of C. annuum was 341.78 mg GAE/g, of C. baccatum 156.76 mg GAE/g, and of C. chinense 107.98 mg GAE/g. Fresh fruits of C. chinense contained 200.17 mg GAE/g of TPC (Sarpras et al, 2018). Comparing with this study, our TPC results showed lower values but we used dried raw.…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…As reported by Bertão et al (2016), TPC in ethanol extracts of C. annuum was 341.78 mg GAE/g, of C. baccatum 156.76 mg GAE/g, and of C. chinense 107.98 mg GAE/g. Fresh fruits of C. chinense contained 200.17 mg GAE/g of TPC (Sarpras et al, 2018). Comparing with this study, our TPC results showed lower values but we used dried raw.…”
Section: Resultscontrasting
confidence: 46%
“…According to Bertão et al (2016), the content of flavonoids in the fruit extracts of C. annuum was 123.56 mg RE/g, of C. baccatum 98.76 mg RE/g, and of C. chinense 67.87 mg GAE/g (RE -rutin equivalent). The fresh fruit of C. chinense had 41.61 mg QE/g of flavonoid content (Sarpras et al, 2018). In the study of Farhoudi et al (2017) Together with flavonoids, the phenolic acids are also an important group of polyphenol compounds in human life that are distinguished as derivatives of benzoic acid and derivatives of cinnamic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Higher dosage of pepper supplements was also found to have adverse effects, such as a slightly prooxidant effect at noncytotoxic concentrations (Huarte et al., 2021) or the ability to cause liver damage (Morittu et al., 2020). Therefore, further studies in future determining the safe dosage of pepper extracts are necessary because pepper extracts display dose‐dependent effects (Sarpras et al., 2018). Jang et al.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The biochemical composition of Capsicum is beneficial not only for plant survival and defense but also for human consumption and health. Through the ages, Capsicum fruits have been consumed widely for their appealing taste as well as medicinal benefits, such as in the treatment of asthma, toothaches, cough, fever, gastrointestinal disorders, skin problems, diabetic neuropathy, and postherpetic neuralgia. In the last two decades, capsaicin and its derivatives have also been explored for their biological and physiological functions, such as metabolism stimulants; antiobesity, anti-inflammatory, and anticancer medications; antioxidants; and analgesics in pharmacological formulations and application . Carotenoids and anthocyanins on the other hand are not only utilized as natural colorants and food additives but also have high antioxidative, anti-inflammatory, antiaging, and skin- and eye-care properties associated with them. The industrial use of Capsicum as dried paprika powder or in the form of oleoresin, which is a concentrated extract of capsaicinoids, flavonoids, carotenoids, and polyphenols obtained from the Capsicum fruits, finds application in food, cosmetics, as well as military purposes …”
Section: Introductionmentioning
confidence: 99%